Intercultural Sensitivity Scale in University Students of Pedagogy Majors in Chile - Contreras-Salinas, S (UNIV COSTA RICA, EDITORIAL, 2022)
The study focused on the validation and application of an intercultural sensitivity scale. The objective of the research was to know and compare the degree of intercultural sensitivity of the different disciplines and level of practice of the pedagogy students of the Faculty of Education of the Central University of Chile, considering for this a division by types of practice (initial, intermediate or professional). The investigators worked with a proportionate stratified random sample, made up of more than 30% of the students of each of the six majors of the Faculty of Education, composed of 227 students University students of this Faculty (19.4% men and 77.1% women), who answered a self-application questionnaire. Initially, a cultural adaptation of the items was carried out with the help of expert judges. For the validation of the scale, a reliability analysis was applied to all the items. After its application to the Chilean sample, the results of validation of the instrument yielded a Cronbach Alpha of .87, concluding that the majors of Differential Education, Basic Education, English and Nursery Education were above the total average of the differentiated, reflecting an adequate intercultural sensitivity, while Education Physics and Mathematics were below this average. In conclusion, the validity and reliability of the instrument is confirmed, as well as its adaptation to the local context. Likewise, the investigators consider that this scale could be used as a valid and reliable measure in Chilean university students of pedagogy, which is also favored by its easy and rapid application.